2011
DOI: 10.1002/jcb.23205
|View full text |Cite
|
Sign up to set email alerts
|

Human periodontal ligament fibroblasts stimulate osteoclastogenesis in response to compression force through TNF-α-mediated activation of CD4+ T cells

Abstract: Periodontal ligament fibroblasts (PLF) sense and respond to mechanical stimuli and participate in alveolar bone resorption during orthodontic treatments. This study examined how PLF influence osteoclastogenesis from bone marrow-derived macrophages (BMM) after application of tension or compression force. We also investigated whether lymphocytes could be a primary stimulator of osteoclastic activation during alveolar bone remodeling. We found that mechanical forces inhibited osteoclastic differentiation from BMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 43 publications
6
69
0
3
Order By: Relevance
“…Alveolar bone resorption can result from excessive compression forces or occlusal stress by stimulation of osteoclastogenesis through local upregulation of RANKL, such as directed resorption on the compression side during orthodontic tooth movement (Walker et al 2008;Wise and King 2008;Sanuki et al 2010;Kook et al 2011 Based on micro-computed tomography, incisor dentin thickness, area, and mineral density were analyzed at (1) alveolar crest, (2) mental foramen, (3) first molar, and (4) third molar. Linear measurements were also performed to determine thickness of incisor enamel, labial and lingual dentin, as well as cross-sectional area of the dentin and enamel.…”
Section: Role Of Altered Mechanotransduction In Bsp -/-Mice Periodontmentioning
confidence: 99%
“…Alveolar bone resorption can result from excessive compression forces or occlusal stress by stimulation of osteoclastogenesis through local upregulation of RANKL, such as directed resorption on the compression side during orthodontic tooth movement (Walker et al 2008;Wise and King 2008;Sanuki et al 2010;Kook et al 2011 Based on micro-computed tomography, incisor dentin thickness, area, and mineral density were analyzed at (1) alveolar crest, (2) mental foramen, (3) first molar, and (4) third molar. Linear measurements were also performed to determine thickness of incisor enamel, labial and lingual dentin, as well as cross-sectional area of the dentin and enamel.…”
Section: Role Of Altered Mechanotransduction In Bsp -/-Mice Periodontmentioning
confidence: 99%
“…In the studies, cytokines have been reported to reflect the local microenvironmental status of periodontal tissues affected by orthodontic forces and to play a key role in the process of bone remodeling that is generated by orthodontic forces [36]. …”
Section: Introductionmentioning
confidence: 99%
“…Kook and Lee (2012) demonstrated that 1.5% elongation tension-stimulated expression of COL I and MMP-1 was controlled by the ERK/JNK-AP-1 and ERK-NF-kB signaling pathways and inhibited the proliferation of human PDL fibroblasts through Ras-p38 MAPK up-regulation. Human PDL fibroblasts stimulate osteoclastogenesis in response to compression force through TNF-alpha-mediated activation of CD4 + T cells (Kook et al, 2011b). Osteopontin expression in mechanical force-subjected PDL fibroblasts was activated by the ERK pathway (Hong et al, 2010).…”
mentioning
confidence: 99%